Different interfacial reactivity of lithium metal chloride electrolytes with high voltage cathodes determines solid-state battery performance. Issue 9 (9th August 2022) - Kochetkov, Ivan; Zuo, Tong-Tong; Ruess, Raffael; Singh, Baltej; Zhou, Laidong; Kaup, Kavish; Janek, Jürgen; Nazar, Linda
Abstract : Comprehensive analysis of all-solid-state cells with NCM85 and a Li-M-Cl catholyte reveals the vital role of the central cation M in controlling the composition of the cathode interphase and dictating capacity retention above 4.3 V. Abstract : A deep understanding of the interaction of the surface of cathode materials with solid electrolytes is crucial to design advanced solid-state batteries (SSBs). This is especially true for the new class of lithium metal chloride (Li-M-Cl) solid electrolytes which are receiving rapidly growing attention due to their very high oxidative stability (>4 V) in combination with good ionic conductivity that can enable long cell cycle life. While Li-M-Cl electrolytes typically contain resource-limited metals (M) such as indium or rare earths, work has focused on substituting M with more abundant elements such as zirconium. Via operando resistance measurements using intermittent current interruption we explore the dynamic evolution of the interphase at the surface of Ni-rich NCM85 or NCM111 cathode particles inside a working SSB with three different Li-(M1, M2 )-Cl catholytes (Li3 InCl6, Li2 Sc1/3 In1/3 Cl4 and Li5/2 Y1/2 Zr1/2 Cl6 ) to reveal the impact of the cationic metal substitution on the interfacial chemistry. We show that the metal plays a critical role in determining high voltage stability, contrary to prior assumptions. Using a combination of cyclic voltammetry and ultraviolet photoelectron spectroscopy measurements of the electronic band structure to assess oxidative stability; coupled with DFT calculations and ToF-SIMS to evaluate products formed at the interface at different upper cutoff potentials and degrees of delithiation, we are able to differentiate between electrochemical and chemical degradation. We find that Li2 Sc1/3 In1/3 Cl4 yields the highest (and Li3 InCl6 the lowest) stability against electrochemical oxidation, while Li5/2 Y1/2 Zr1/2 Cl6 undergoes a detrimental chemical reaction with oxygen released from Ni-rich NCM85 at high potentials, resulting in fast capacity fading. Overall, our work establishes a platform for the metrics and an approach that can be utilized to efficiently evaluate the stability of new halide SEs in SSB cells.